2020
DOI: 10.1002/ejic.202000150
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoropyridine as an Efficient, Tunable Scaffold for Bis(pyrazol‐1‐yl)pyridine Copper Complexes

Abstract: This report details the syntheses of five new 2,6bis(pyrazol-1-yl)pyridine ligands carried out by a unique strategy of utilizing pentafluoropyridine for the pyridine core. Formation of each ligand is accomplished under mild conditions utilizing carbonate bases. Each ligand reacts readily with copper(II) triflate to form the corresponding salt in high yield. Ligands and complexes were characterized by a combination of multi-nuclear NMR, FTIR, UV/Vis, and single-crystal X-ray diffrac- [a] Scheme 1. Synthetic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…While most of our molecular weights were consistent with a chain-growth mechanism, our Đ ’s were large relative to what is normally obtained for ROMP chain-growth polymerizations as shown in Table (for poly1 systems) and Table (for poly3 systems). While we are uncertain of the exact cause of these relatively high Đ ’s, this behavior was attributed to the potential coordination of the fluoropyridine ring to the ruthenium catalyst during the initiation step allowing the propagation step to progress significantly before the initiation step could go to completion, a factor that is well known to cause relatively high Đ ’s in chain-growth processes. Previous work has demonstrated that the nitrogen of the fluoropyridine ring can participate in metal coordination making this a plausible, possible explanation . Postmodification of poly1 was carried out exclusively in THF with the exception of the installations of 4-nitrophenol and propargyl alcohol which required DMF to be used as the solvent.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of our molecular weights were consistent with a chain-growth mechanism, our Đ ’s were large relative to what is normally obtained for ROMP chain-growth polymerizations as shown in Table (for poly1 systems) and Table (for poly3 systems). While we are uncertain of the exact cause of these relatively high Đ ’s, this behavior was attributed to the potential coordination of the fluoropyridine ring to the ruthenium catalyst during the initiation step allowing the propagation step to progress significantly before the initiation step could go to completion, a factor that is well known to cause relatively high Đ ’s in chain-growth processes. Previous work has demonstrated that the nitrogen of the fluoropyridine ring can participate in metal coordination making this a plausible, possible explanation . Postmodification of poly1 was carried out exclusively in THF with the exception of the installations of 4-nitrophenol and propargyl alcohol which required DMF to be used as the solvent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…18−20 Previous work has demonstrated that the nitrogen of the fluoropyridine ring can participate in metal coordination making this a plausible, possible explanation. 21 Postmodification of poly1 was carried out exclusively in THF with the exception of the installations of 4-nitrophenol and propargyl alcohol which required DMF to be used as the solvent. Analysis of both premodified and postmodified polymers via 1 H and 19 F NMR showed successful polymerization and successful incorporation of the desired functionalities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chemicals and solvents, which were of reagent grade, were purchased through commercial suppliers and used as received, unless specifically noted. The synthesis of 5 , 7 , and 8 was carried out from previously published work. , …”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of 5, 7, and 8 was carried out from previously published work. 31,34 Instrumentation. 1 H, 13 C, and 19 F NMR spectra were recorded on a JEOL 500 MHz spectrometer.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation